Rojas Martínez, Olga Lorena, Paternidad y vida familiar en la Ciudad de México, México, El Colegio de México, 2008, 231 p. - García, Brígida (Estudios Demográficos y Urbanos, 2008)
Rojas Martínez, Olga Lorena. (2008). Paternidad y vida familiar en la Ciudad de México, México, El Colegio de México, A.C.